Prediction Models of the Sele-Harm for Psychiatric Patients using Data Mining Techniques - Samart, Sopita; Thongkam, Jaree (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
The objective of this research is to create and compare the effectiveness of a self-harm model for psychiatric patients. The data were collected from Khon Kaen Rajanagarindra Psychiatric Hospital database, Khon Kaen province from January 2019 to December 2021. The records were 4,179 records in total. Gain Ratio and Relief methods were used to select relevant factors for building the prediction models. Naive Bay, Decision tree, Machine support, Deep learning, Partial rule techniques were utilized to build self-harm in psychiatric patients prediction models. In this experiment, 10-fold cross validation was used to divide the data into learning and testing datasets. Accuracy, sensitivity, and specificity were employed to compare the effectiveness of the models. The experimental results showed that selection of factors using the Gain Ratio method when used C4.5 decision tree or machine support vector machine techniques has the same highest accuracy at 84.66 %.